Implementasi Bahan Ajar Pokok Bahasan Aljabar Menggunakan Model Pembelajaran Mind Mapping dengan Pendekatan Saintifik (Universitas Dr. Soetomo, 2023)
Mathematics is studied in Indonesia at all school levels because it is able to train students' problem-solving skills and meet practical demands. Teachers and students still face a lot of challenges in putting these strategies into practice, though. The fact that the course material did not adhere to the approaches and models that attracted and engaged students was one of the problems. The 2013 curriculum aims to develop productive, inventive, creative, and character-defining learners by integrating the development of attitudes, abilities, and knowledge. The mind-mapping learning paradigm has the power to inspire pupils, excite them, and pique their interest in the content they are studying. In order to create educational materials employing a mind mapping methodology with a scientific approach, developmental research is also required. A stage known as implementation is necessary for the proper production and distribution of the development material. This study concentrates on the implementation phase to evaluate the usefulness and potency of the information. In one of Kupang's upper secondary schools, the eighth grade saw the implementation of instructional materials. Based on the outcomes of the data analysis, it was determined that each meeting's criteria for teacher and student learning activity fell into the